Growth and yield of chilli (Capsicum annuum L.) in response to mulching and potassium fertilization - Hassan, Siti Aishah; Zainal Abidin, R.; Ramlan, Mohd Fauzi (Universiti Putra Malaysia Press, 1995)
A field experiment was canducted 10 study the influence of levels of potassium fertilizer (0, 66 and 132 kg ha-1) and types of mulching (black plastic, reflective plastic and coconut fronds) on growth and yield of chilli. Plant height, yield, fruit number and dry weight of plant increased with increasing K levels and mulching. Yields were increased by 89% and 142% with K levels of 66 and 132 kg ha-1, respectively. Highest yield was obtained from plant grown under reflective plastic mulch. Nitrogen, P, K and Ca content in leaf tissues, soil temperature and moisture under mulched conditions were higher than without mulch. There was a positive correlation between plant dry weight with soil temperature and moisture.